FACTORS DIRECTLY AND INDIRECTLY AFFECTING TO THE NATIONAL STATE SOVEREIGNTY IN THE CONTEXT OF GLOBALIZATION - Hamroyev Sanjar Samiyevich (PT ANTIS INTERNATIONAL PUBLISHER, 2023)
The total achievements of mankind today are a continuation of the evolution of ancient civilizations and are developing at an unprecedented rate due to the intensity of globalization in all spheres of society. It is well known that globalization is a huge reality of our time, and it is increasingly having its dichotomous, ie dual, sometimes positive, sometimes negative impact not only on the economy, but also on politics, spirituality, culture and social life. Although globalization is not a reality of the present period, its coexistence with time is characterized by the fact that in a given period new problems arise unpredictably and require the solution of these problems. Otherwise, these problems are likely to lead to the decline of the whole of humanity. For example, the fact that the epidemic that started in 2019 in China's Wuhan province soon became a global pandemic proves that the destinies of humanity and nations are closely intertwined, and that in the context of globalization, interstate and interethnic solidarity prevails. This article provides a political and philosophical analysis of the means directly and indirectly affect the national-state sovereignty in the context of globalization, including external debt, membership in international organizations, lack of natural resources, enclaves and exclaves, increasing military capacity of neighboring countries, media, art, special attention is paid to tools that affect sovereignty, such as the education system, Internet resources, and transnational corporations